1985
DOI: 10.1083/jcb.101.4.1386
|View full text |Cite
|
Sign up to set email alerts
|

Temporal coincidence between synaptic vesicle fusion and quantal secretion of acetylcholine.

Abstract: We applied the quick-freezing technique to investigate the precise temporal coincidence between the onset of quantal secretion and the appearance of fusions of synaptic vesicles with the prejunctional membrane. Frog cutaneous pectoris nerve-muscle preparations were soaked in modified Ringer's solution with 1 mM 4-aminopyridine, 10 mM Ca 2+, and 10 -4 M d-Tubocurarine and quick-frozen 1-10 ms after a single supramaximal shock. The frozen muscles were then either freeze-fractured or cryosubstituted in acetone wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(60 citation statements)
references
References 49 publications
(84 reference statements)
4
56
0
Order By: Relevance
“…It has been proposed that synaptic vesicles also can reseal after they release transmitter (20,39). In this model of exocytosis, the vesicle does not exchange membrane components with the plasma membrane (21).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that synaptic vesicles also can reseal after they release transmitter (20,39). In this model of exocytosis, the vesicle does not exchange membrane components with the plasma membrane (21).…”
Section: Discussionmentioning
confidence: 99%
“…After 1 h, they were washed carefully and then postfixed for an additional hour with cold 2% OS04 in 0.12 M phosphate buffer, pH 7.3. Dehydration, infiltration, and embedding in Araldite were done as described previously (Watanabe et al, 1983 (Torri Tarelli et al, 1985). Frozen specimens were then transferred into an ultra-highvacuum chamber (Cryofract 190) and freeze-dried under controlled conditions as described previously (Grohovaz et al, 1996).…”
Section: Materials and Methods Cell Preparationmentioning
confidence: 99%
“…Although recent quick-freeze studies of frog terminals treated with 4-aminopyridine have demonstrated that vesicles fuse with the presynaptic membrane a few milliseconds after the arrival of a single nerve impulse (Heuser, Reese, Dennis, Jan, Jan & Evans, 1979;Torri-Tarelli, Grohovaz, Fesce & Ceccarelli, 1985), controversy still exists over whether the secreted quanta represent ACh that is released from the interiors of the fused vesicles (Tauc, 1982). An alternative hypothesis is that the quanta represent axoplasmic ACh which diffuses in pulses through channels in the presynaptic membrane that become transiently permeable to it (Tauc, 1982;Israel & Manaranche, 1985).…”
Section: Introductionmentioning
confidence: 99%